A Fault Current Limiter Circuit to Improve Transient Stability in Power System - Saumen Dhara; Alok Kumar Shrivastav; Pradip Kumar Sadhu; Ankur Ganguly (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Short circuit current limitation in distribution system utilities can be an operational approach to improve power quality, since the estimated voltage sag amplitude during faults may be intensely reduced. The application of superconducting fault current limiter (SFCL) is projected here to limit the fault current that occurs in power system. SFCL utilizes superconductors to instantaneously decrease the unanticipated electrical surges that happen on utility distribution and power transmission networks. SFCL considerably decrease the economic burden on the utilities by reducing the wear on circuit breakers and protecting other expensive equipment. The designed SFCL model is used for determining an impedance level of SFCL according to the fault current limitation necessities of different types of the smart grid system. The representation of this paper about to see the optimum resistive value of SFCL for enhancing the transient stability of a power system. The assessment of optimal resistive value of the SFCL connected in series in a transmission line with a conductor throughout a short circuit fault is consistently determined by applying the equal-area criterion supported by power-angle curves. A Simulink based primary model is developed and additionally the simulation results for the projected model are achieved by using MATLAB.